Faith and Evaluation: Catholic Religious Education in a Plural Society - Bawa Toron, Vinsensius; Dancar, Aleksander; Marzuki, Marzuki; Muhson, Ali (UIN Sunan Gunung Djati Bandung, 2024)
This study explores assessment practices in Catholic religious education across junior secondary schools in Indonesia, with the primary aim of understanding how teachers evaluate student learning in plural and culturally diverse contexts. Set against the backdrop of Indonesia’s multicultural society, the research addresses the growing need for inclusive, value-based, and contextually adapted religious education. Employing a qualitative narrative phenomenological approach, the study draws upon semi-structured interviews with six Catholic religious education teachers from Western, Central, and Eastern Indonesia. Supplemented by curriculum documents and analysed using thematic analysis with ATLAS.ti, the research captures teachers’ lived experiences and assessment strategies. The findings reveal that teachers employ a hybrid model of evaluation—combining written tests, projects, discussions, and reflections—that aligns with students’ social realities and moral development. Assessment is used not only to measure knowledge, but also to reinforce ethical behaviour, religious tolerance, and community engagement. The study highlights the importance of parental involvement, technological integration, and context-responsive pedagogy in enhancing learning outcomes. The implications suggest that Catholic religious education can play a strategic role in promoting social cohesion and intercultural understanding in a plural society. This research contributes original insights by providing a regionally comparative and empirically grounded account of assessment in faith-based education, emphasising the role of teacher agency in navigating doctrinal integrity and multicultural sensitivity.